Early career values and individual factors of objective career success: The case of the French business graduates. Issue 4 (12th August 2019) - Giraud, Laurent; Bernard, Alain; Trinchera, Laura
Abstract : Purpose: The purpose of this paper is to investigate the early career values and individual factors of objective career success among graduates from a top-tier French business school. Design/methodology/approach: The authors conducted a quantitative analysis of 629 graduates classified in three job markets according to income: the traditional business market, the alternative market and the high-potential business market. The graduation dates span a period of 12 years before the 2008 Recession. Findings: The findings suggest that membership of each job market is associated with distinct early career values (when choosing/leaving the first job). Moreover, the authors confirm that the presence of a mentor, international experience, job-hopping and gender, all affect objective career success. Practical implications: The paper discusses implications for business career development and higher business education. Originality/value: The originality of this study lies in the identification of the individual factors of objective career success among French business graduates and the links between objective career success and early career values.